Acquired Basic and Integrated Science Process Skills and Academic Performance in Earth Science of Grade 11 Students in a Philippine Public High School - Jardinico III, Evenizer C.; Linaugo, Joji D. (Philippine Social Science Journal, 2023)
The Philippine Department of Education requires Science Process Skills (SPS) to be incorporated into studying or teaching science at all levels of learning in basic education. This study investigated the relationship between the level of acquired basic and integrated Science Process Skills (SPS) and academic performance in Earth Science of Senior High School STEM students. Through descriptive and inferential analyses, the result showed no significant relationship between acquired integrated science process skills and academic performance in Earth Science. However, a significant relationship between acquired basic science process skills and academic performance in Earth Science was yielded. The findings revealed that students must first develop a strong foundation in basic science process skills to develop more advanced science process skills. Hence, the task cards, as supplementary instructional materials, may provide students with a structure to focus their search and strengthen their independent learning skills.